Explaining the Diffusion of Renewable Energy Technology in Developing Countries - Birte Pohl; Peter Mulder (German Institute of Global and Area Studies (GIGA), 2013)
In this paper we study the diffusion of non-hydro renewable energy (NHRE) technologies for electricity generation across 108 developing countries between 1980 and 2010. We use two-stage estimation methods to identify the determinants behind the choice of whether or not to adopt NHRE as well as about the amount of electricity to produce from renewable energy sources. We find that NHRE diffusion accelerates with the implementation of economic and regulatory instruments, higher per capita income and schooling levels, and stable, democratic regimes. In contrast, increasing openness and aid, institutional and strategic policy support programs, growth of electricity consumption, and high fossil fuel production appear to delay NHRE diffusion. Furthermore, we find that a diverse energy mix increases the probability of NHRE adoption. Finally, we find weak support for a positive influence of the Kyoto Protocol on NHRE diffusion and no evidence for any influence resulting from financial sector development.
Keywords: O13; O14; Q42; Q48; 330; renewable energy technologies; developing countries; electricity; technology diffusion; sample selection